Assessment of the current status of pesticide use in triple-rice crops in Hoa Long commune, Lai Vung district, Dong Thap province, Vietnam - Giao, Nguyen Thanh (International Journal of Environment, Agriculture and Biotechnology, 2020)
This study was implemented to evaluate the current status of pesticide use in triple rice cropping in Hoa Long commune, Lai Vung district, Dong Thap province, Vietnam. The findings showed that the common pesticides used by the farmersin the study area belonging to toxicity Group II and III (World Health Organization (WHO) classification) accounted for 67.6%. Some farmers also usedpesticides containing banned active ingredients such as 2.4D, carbosulfan and carbendazole. The frequency of pesticide use was 5.5 times/crop which was relatively high. Basing on the active ingradientcompounds present in the study area, the potential environmental impact of pesticides is very seriously. The farmers used masks when spraying pesticides, however, they did not have a full understanding of the harmful effects of pesticide exposure. Packaging and bottles of pesticides after use have not been collected and disposed appropriately;it was commonly thrown away in the canals, ditches, and bare land after use. Local authorityhas not yet taken comprehensive measures to completely handle pesticide packaging and bottles due to funding constraints. In order to reduce the environmental and health risks associated with the use of pesticides and its wastes in the study area, local authority needs to increase the propaganda of knowledge about the management and use of pesticides while developing appropriate program for effective management of pesticidewastes.